Quantitative Two-Weight Boundedness for Iterated Commutators of Multilinear Fractional Operators With Lα,r′-Hörmander Conditions - Zhidan Wang; Chunmei Zhang (Journal of Function Spaces)
In this paper, we investigate the quantitative two-weight boundedness for iterated commutators of multilinear fractional operators with Lα,r′-Hörmander conditions. The analysis relies heavily on sparse domination techniques for the operators. We extend the result already established to the multilinear setting and to iterated commutators.